Pembuatan Sistem Informasi Produksi Ikan Konsumsi Berbasis Java Di Kabupaten Kampar - Fadli Julianto Erga; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Kampar is a regency in Riau Province which economic activities depend on fisheries. A problem that exists in Kampar’s fisheries is an imbalance in the amount of fish production with the amount of fish needed by the community. To help Kampar Fisheries Department employees to overcome these problems, a Java-based Information System and an Android-Based Information System will be created. To create the information system, Netbeans and Android Studio software with Java language are needed. The method used in this research is a waterfall where each stage of the research is carried out sequentially. The result of this research is an information system that provides specific data so that it can facilitate employees of the Kampar Fisheries Department employees to balance the amount of fish production with the amount of fish needed by the community.Keywords: Information System, Fish Production, Java, Kampar